Inequality and specialization: the growth of low-skill service jobs in the United States - David H. Autor; David Dorn (Institute for the Study of Labor (IZA), 2009)
After a decade in which wages and employment fell precipitously in low-skill occupations and expanded in high-skill occupations, the shape of U.S. earnings and job growth sharply polarized in the 1990s. Employment shares and relative earnings rose in both low and high-skill jobs, leading to a distinct U-shaped relationship between skill levels and employment and wage growth. This paper analyzes the sources of the changing shape of the lower-tail of the U.S. wage and employment distributions. A first contribution is to document a hitherto unknown fact: the twisting of the lower tail is substantially accounted for by a single proximate cause - rising employment and wages in low-education, in-person service occupations. We study the determinants of this rise at the level of local labor markets over the period of 1950 through 2005. Our approach is rooted in a model of changing task specialization in which routine clerical and production tasks are displaced by automation. We find that in labor markets that were initially specialized in routine-intensive occupations, employment and wages polarized after 1980, with growing employment and earnings in both high-skill occupations and low-skill service jobs.
urn:nbn:de:101:1-20090824183
Keywords: E24; J24; J31; J62; O33; 330; Skill demand; job tasks; inequality; polarization; technological change; occupational choice; Arbeitsmarkt; Qualifikation; Ungelernte Arbeitskräfte; Lohn; Beschäftigung; Arbeitsmarktungleichgewicht; Strukturwandel; USA